Designing for All: Embedding Universal Design for Learning (UDL) with AI‑enabled Networked Practice - Carson, Julie; Benfield, Hollie; Caldwell, Debbie (Proceedings of the International Conference on Networked Learning, 2026)
This workshop is designed for educators, researchers and leaders across primary, secondary and higher education who are committed to inclusion, accessibility and digital transformation. While the practical examples are drawn from primary education, the workshop deliberately focuses on design principles, networked professional learning practices and technology-enabled UDL strategies that are transferable across educational phases, including secondary and higher education. Participants seeking to understand how technology and Artificial Intelligence (AI) can be used to design for learner diversity from the outset, and how digital pedagogy and networked learning practices support and sustain pedagogical change, will find this workshop highly relevant.